The Response of Lettuce (Lactuca sativa L.) to The Types and Application Time of Agroprobiotic Fertilizer - Alvera Prihatini Dewi Nazari; Eliyani Eliyani; Wilujeng Astutik (Universitas 17 Agustus 1945 Samarinda, 2019)
The Response of Lettuce (Lactuca sativa L.) to The Types and Application Time of Agroprobiotic Fertilizer. Agroprobiotic fertilizer as an alternative of organic fertilizer is expected to reduce the use of chemical fertilizers. The aim of the study was to determine: (1) the best type of agroprobiotic fertilizer; (2) the best application time; (3) interaction between the two factors on the growth and yield of lettuce. The study was conducted from May until July 2018 at Faculty of Agriculture, Mulawarman University. The research was 5x2 factorial experiment arranged in Completely Randomized Design with six time replications. The first factor was the types of agroprobiotic fertilizer, namely: Maknyus; Cimelati; Mayas Putih; Keriting; and Hitam rice. The second factor was the application time of fertilizer, consisted of: in the morning (at 07.00-08.00) and in the afternoon (at 17.00-18.00). The variables observed consisted of: the increment of plant height and number of leaves increment at 14; 28; 42 days after treatment (DAT); and at harvest time, fresh weight, and leaves area. Data were analyzed by analysis of variance and continued with the Least Significant Difference (LSD) test at 5% level. The results showed that the types of agroprobiotic fertilizer and the interaction between the two factors had no significantly different on the growth and yield of lettuce. Agroprobiotic fertilizer from Mayas Putih rice showed the better growth and yield than others. The best time for application of fertilizer was in the morning, it showed significantly different on the increment of plant height at harvest time.